PRAKTIKALITAS MULTIMEDIA INTERAKTIF MEDAN MAGNET SEBAGAI MEDIA PEMBELAJARAN FISIKA KELAS XII SMA - Dhia Hana Mufida; M. Rahmad '; Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: The purpose of this study discovered the practicalities of multimedia from the research that has been done about validation and development of magnetic field interactive multimedia using Adobe Flash. There are 17 students and 5 teachers from senior high school in Pekanbaru has participated in this research. The design of this study was Research and Development (R&D). The first step was preliminary study, multimedia design, multimedia manufacture, multimedia validation, multimedia revision, valid multimedia, practicalities, finally produced valid and practical multimedia. In the research of practicalities, it used experiment methods with Single One Shot Case Study model. Practicalities data has been taken from questionnaire and interview with the teachers and students. Descriptive analysis has been used for knowing practicality of magnetic field interactive multimedia. The results has indicated that the text, graphics, color, animation, audio, video, navigation, and background in multimedia is practical to read, understand, and observe. This has been shown by average score of the valuation indicator 3.40 to teachers and 3.27 to students with very high category. The practicality results also has been supported by interview with the same result, that magnetic field interactive multimedia practical to use in magnetic field learning.Key Words: Practicalities, Magnetic Field Interactive Multimedia, Adobe Flash.